Positive Affirmation Exercises Against Reducing Anxiety In Facing Vaccination Covid-19 - Firmawati Firmawati; Nur Uyuun I. Biahimo; Cindra Umar Hasan; Yunitro Ibrahim; Yulianti Yunus (Pusat Studi Pembangunan dan Pemberdayaan, 2021)
Vaccination is a process that occurs in the human body that will become immune or can be protected from various diseases. Since the establishment of COVID-19 as a pandemic, there have been various changes in the pattern of human life. This impact can trigger stress in society. Coupled with the emergence of some Vaccine related misinformation that hinders preventive measures. Anxiety is a natural psychological condition felt by individuals when they feel a threat to things that are not clear. Many methods have been used to reduce anxiety, one of which is the positive affirmation technique. Positive affirmations are hopes, prayers, aspirations to help form a picture in one's thinking power or self-acceptance statements (Abdurrahman, 2012). The people who were given community service training were the people of the village of Bulota, Talaga Jaya sub-district. Based on the results of the training, it shows that most of the community stated that this training was very useful because they gained knowledge and understanding of dealing with anxiety when administering the covid-19 vaccine